Environmental Performance as a Legitimacy Signal: Strengthening or Weakening the Effect on Financial Outcomes? - Azizah, Laila Oshiana Fitria; Chang, Chia-Hua (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study examines the relationship between Corporate Social Responsibility (CSR) and financial performance, with a particular focus on the moderating role of environmental performance. Grounded in legitimacy theory, the study aims to investigate whether environmental performance strengthens or weakens the financial benefits derived from CSR activities in the context of Indonesian listed firms.Methodology: The study employs a quantitative explanatory research design using panel data from manufacturing firms listed on the Indonesia Stock Exchange during the period 2021-2024. CSR is measured using a CSR Disclosure Index based on Global Reporting Initiative (GRI) standards, while environmental performance is assessed using the Indonesian government’s PROPER rating system. Financial performance is proxied by Tobin’s Q. Moderated Regression Analysis (MRA) is applied to test the direct effects of CSR and environmental performance on financial performance, as well as the interaction effect between CSR and environmental performance. Results: The findings indicate that CSR has a significant positive effect on financial performance, supporting the view that socially responsible practices enhance corporate legitimacy and firm value. Environmental performance also shows a positive direct effect on financial outcomes. However, the interaction between CSR and environmental performance reveals a significant negative moderating effect, suggesting that high environmental performance reduces the incremental financial benefits of CSR, indicating a substitution rather than a reinforcement effect. Applications/Originality/Value: This study extends legitimacy theory by demonstrating that sustainability signals may interact in complex and non-linear ways. It provides valuable insights for managers, investors, and policymakers by highlighting the importance of strategically balancing CSR and environmental initiatives rather than assuming their effects are always complementary.